Mudança estrutural e dinâmica do mercado de trabalho no Brasil - Pinto, Ana Cleide Rocha (2024)
This paper investigates the evolution of productivity in the Brazilian economy from 1951 to 2018, using a shift-share decomposition methodology to analyze productivity changes within economic sectors. The study focuses on identifying and assessing the internal, static, dynamic, and unexplained effects that influenced productivity during various periods marked by significant economic reforms and challenging global contexts. The analyzed data, sourced from the Groningen Growth and Development Centre, cover periods from 1950 to 2014 and from 1990 to 2018, detailing changes across up to 12 economic sectors. The examined data reveal how the combined effects of these four components shaped Brazil's economic development over nearly seven decades. In particular, the analysis details how specific events, such as the implementation of the Plano Real and the global financial crisis of 2008, impacted these effects and, consequently, economic productivity. The study highlights that, in addition to macroeconomic reforms, factors such as governmental policies, international crises, and the internal dynamics of the labor market played crucial roles in shaping the economy. These findings point to the need for well-targeted economic policies that can promote sustainable productivity, taking into account the intrinsic complexities and demands of an ever-changing global environment.